(untitled) (Global Journal of Human-Social Science, 2025)
In the state of Goi s the beef production chain plays a central role in the regional economy but faces significant challenges in integrating sustainable practices that align with Environmental Social and Governance ESG criteria and the United Nations Sustainable Development Goals SDGs This study aims to investigate how these frameworks are currently being addressed within the sector and to identify opportunities for improving sustainability performance Through a comprehensive literature review and analysis of organizational and institutional data the research mapped the current state of knowledge revealing a scarcity of academic studies focused specifically on ESG practices in beef production While several initiatives aligned with environmental management and the SDGs have been identified the effective incorporation of ESG criteria remains limited The findings indicate that although some sustainable practices are emerging particularly in response to public policies and technological innovation significant gaps persist especially in social and governance dimensions The research emphasizes the need for an integrated approach that goes beyond environmental compliance incorporating responsible governance social accountability animal welfare and efficient resource use The study concludes by highlighting that a shift toward innovative inclusive and sustainable business models is crucial for the long-term competitiveness and resilience of the beef sector in Goi s The proposed strategies aim to strengthen the sector s ability to meet growing market demands for responsible production while also contributing to local development and the preservation of natural ecosystems